2011
DOI: 10.1536/ihj.52.348
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Outcomes Among Patients With Diabetes Mellitus After Percutaneous Coronary Intervention in the Drug-Eluting Stent Era

Abstract: SummaryDiabetes mellitus has a greater effect on mortality rates due to coronary artery disease in women than in men. Although women undergoing coronary intervention in general have a higher frequency of adverse outcomes than men, the effect of gender among diabetic patients on clinical outcomes after percutaneous coronary intervention (PCI) has not been well established in the drug-eluting stent (DES) era. We have investigated the impact of gender on long-term clinical outcome in these high risk populations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…In contrast, a recent study that enrolled only patients with diabetes in Japan found that at 4-year follow-up after PCI, the cumulative incidence of MACE was similar between the sexes, despite the fact that women had a worse baseline profile. 20 Similar to our study, a significant interaction was observed by Mehilli et al, who evaluated the impact of sex on mortality after PCI in a cohort of patients with stable and unstable angina. 12 They reported that diabetic women had almost twice the mortality hazard in comparison to diabetic men, whereas no significant difference was observed in mortality among the non-diabetic population.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, a recent study that enrolled only patients with diabetes in Japan found that at 4-year follow-up after PCI, the cumulative incidence of MACE was similar between the sexes, despite the fact that women had a worse baseline profile. 20 Similar to our study, a significant interaction was observed by Mehilli et al, who evaluated the impact of sex on mortality after PCI in a cohort of patients with stable and unstable angina. 12 They reported that diabetic women had almost twice the mortality hazard in comparison to diabetic men, whereas no significant difference was observed in mortality among the non-diabetic population.…”
Section: Discussionsupporting
confidence: 89%
“…Our results and the results reported by Ogita et al, 7 Shrestha et al, 17 Buja et al, 18 Stefanini et al, 19 Funakoshi et al, 20 Kralev et al, 21 and Lansky et al 22 suggest that DES have leveled the playing field between diabetic males and females undergoing PCI. The acute angiographic success and clinical outcomes are similar between males and females, despite advanced age and more co-morbidities in the latter.…”
Section: Discussionsupporting
confidence: 74%
“…Funakoshi et al 20 reported no significant gender difference in the incidence of MACEs at a 3-year follow up period of the Japanese CREDO-Koyato registry; the rate of all cause death and ACS among women in that registry was 4.3% and 8.4%, respectively. Ogita et al 7 showed no significance difference in the PCI outcome among men and women after elective drugeluting stent implantation in diabetic patients. Kralev et al 21 reported that female gender did not emerge as an independent predictor of MACEs despite the worse baseline clinical features seen in females.…”
Section: Discussionmentioning
confidence: 96%
“…A few studies, such as the large Asia Pacific Cohort Studies Collaboration (2), did not show any difference between sexes in deaths from CHD, cerebrovascular disease or other CVDs, irrespective of ethnicity. Moreover, although these studies have considered the risk of CVD events in those initially free of CVD, some authors found no sex difference according to DM in risk of recurrent CVD in women and men with existing CVD (8).…”
Section: Introductionmentioning
confidence: 98%